Superior Vena Cava (SVC) Endovascular Reconstruction with Implanted Central Venous Catheter Repositioning for Treatment of Malignant SVC Obstruction - Volpi, Stephanie; Doenz, Francesco; Qanadli, Salah D. (Frontiers in Surgery, 2018)
Superior vena cava (SVC) syndrome is a group of clinical signs caused by obstruction or compression of SVC and characterized by edema of the head, neck, and upper extremities, shortness of breath, and headaches. The syndrome may be caused by benign causes but most of the cases are caused by lung or mediastinal malignant tumors. Stenting of SVC has become widely accepted as palliative treatment for this condition in malignant diseases as it offers rapid relief of symptoms and improves quality of life. Preserving previously placed central venous catheters (CVC) is a major issue in this population. We report the case of a patient with SVC syndrome caused by tumoral obstruction due to central small-cell lung cancer who had right subclavian implanted CVC and a preferential head and neck venous drainage through the left internal jugular and brachiocephalic vein (BCV). We describe a complex procedure of SVC reconstruction with two different objectives; left recanalization and stent placement to ensure head and neck venous drainage and right BCV stenting for CVC repositioning and subsequent replacement. We also reviewed published cases of SVC obstructions stenting with catheter repositioning. The patient experienced quick relief of symptoms after treatment. Chemotherapy was rapidly delivered through the preserved implanted CVC access. Three-months follow-up computed tomography (CT) showed stents patency.